The impact of thyroid hormones on patients with hepatocellular carcinoma. - Matthias Pinter; Lukas Haupt; Florian Hucke; Simona Bota; Theresa Bucsics; Michael Trauner; Markus Peck-Radosavljevic; Wolfgang Sieghart (PLoS ONE)
Background & aims Hypothyroidism has recently been proposed as predisposing factor for HCC development. However, the role of thyroid hormones (TH) in established HCC is largely unclear. We investigated the impact of TH on clinical characteristics and prognosis of HCC patients. Methods Of 838 patients diagnosed with nonsurgical HCC at the Division of Gastroenterology and Hepatology/Medical University of Vienna between 1992 and 2012, 667 patients fulfilled the inclusion criteria. The associations of thyroid function tests with patient, liver, and tumor characteristics as well as their impact on overall survival (OS) were investigated. Results Thyroid hormone substitution was more often observed in patients with low thyroid-stimulating hormone (TSH) concentration and in patients with elevated free tetraiodthyronine (fT4). Patients with high TSH (>3.77uU/ml) concentrations had larger tumors, while the opposite was true for patients with low TSH (<0.44uU/ml) concentrations. Subjects with elevated fT4 (>1.66ng/dl) were more likely to have elevated CRP. While TSH was only associated with OS in univariate analysis (≤1.7 vs. >1.7uU/ml, median OS (95%CI), 12.3 (8.9-15.7 months) vs. 7.3 months (5.4-9.2 months); p = 0.003), fT4 (≤1.66 vs. >1.66ng/dl, median OS (95%CI), 10.6 (7.5-13.6 months) vs. 3.3 months (2.2-4.3 months); p = 0.007) remained an independent prognostic factor for OS (HR (95%CI) for fT4>1.66ng/dl, 2.1 (1.3-3.3); p = 0.002) in multivariate analysis. Conclusions TSH and fT4 were associated with prognostic factors of HCC (i.e., tumor size, CRP level). Elevated fT4 concentrations were independently associated with poor prognosis in HCC. Further studies are needed to characterize the role of TH in HCC in detail.